2008
DOI: 10.4049/jimmunol.180.10.6611
|View full text |Cite
|
Sign up to set email alerts
|

Administration of PLP139–151 Primes T Cells Distinct from Those Spontaneously Responsive In Vitro to This Antigen

Abstract: We examined the TCR repertoire used by naive SJL mice in their in vitro spontaneous response to proteolipid protein (PLP) 139–151 by Vβ-Jβ spectratyping and compared it to that used after immunization with the peptide. T cells from immunized mice use the public rearrangement Vβ10-Jβ1.1, but naive mice do not; in contrast, TCR CDR3-β rearrangements of Vβ18-Jβ1.2 and Vβ19-Jβ1.2 consistently are associated with the spontaneous response. T cells involved in spontaneous and induced responses can each recognize PLP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 74 publications
5
37
0
Order By: Relevance
“…3A, right column). This frequency is comparable to that seen in SJL mice after immunization with p139 in adjuvant as previously reported (6) and confirmed in this study by the data reported in the same Fig. 3A (one positive of four mice injected with p139 in adjuvant; Fig.…”
Section: Infection With Live Rmssupporting
confidence: 93%
See 3 more Smart Citations
“…3A, right column). This frequency is comparable to that seen in SJL mice after immunization with p139 in adjuvant as previously reported (6) and confirmed in this study by the data reported in the same Fig. 3A (one positive of four mice injected with p139 in adjuvant; Fig.…”
Section: Infection With Live Rmssupporting
confidence: 93%
“…The spontaneous repertoire was depleted at the same time also from the spleens (data not shown). These data are consistent with the hypothesis that the p139-specific spontaneous repertoire was recruited and in part already depleted by rMS p139 to a similar extent as that seen following immunization with p139 in adjuvant (6).…”
Section: Infection With Live Rmssupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly, we have shown that T cell repertoires are different in pathogenic and nonpathogenic autoimmune responses in human disease and experimental models (40,46). We therefore asked if cell localization ( H PE-⌬MPT64-BCG versus H ⌬MPT64-BCG) and amount of antigen produced ( H PE-⌬MPT64-BCG versus 33 PE-⌬MPT64-BCG) impact T cell repertoire selection and if differences in the composition of the MPT64-specific repertoire were correlated with protection.…”
Section: Pe-⌬mpt64-bcg Correlates With the Induction Of Ifn-␥ Expressmentioning
confidence: 99%